Assessing the scientific research productivity of a leading toxicology journal: A case study of Human & Experimental Toxicology from 2003 to 2012 - Zyoud, Sa’ed H (SAGE Open Med, 2014)
BACKGROUND: Bibliometric studies are increasingly being used for research assessments. Bibliometric indicators involve the application of statistical methods to scientific publications to obtain the bibliographics for each journal. The main objective of this study was to conduct a bibliometric evaluation of Human & Experimental Toxicology retrieved from the Scopus database. METHODS: This study obtained data from Scopus published from 1 January 2003 till 31 December 2012. The keywords entered in Scopus to accomplish the objective of this study were ‘Human’, ‘Experimental’ and ‘Toxicology’ as ‘Source Title’. Research productivity was evaluated based on a methodology developed and used in other bibliometric studies by analysing (a) total and trends in Human & Experimental Toxicology contributions in research between 2003 and 2012; (b) Human & Experimental Toxicology authorship patterns and productivity; (c) collaboration patterns; and (d) the citations received by the publications. RESULTS: There were 1229 research articles published in Human & Experimental Toxicology. Of the articles included, 947 (77.1%) were original articles and 104 (8.5%) were review articles. The Hirsch-index of the retrieved documents was 35. The largest number of publications in Human & Experimental Toxicology was from the United States (19.6%), followed by India (12.8%) and Turkey (10.9%). The total number of citations was 9119, with a median (interquartile range) of 3 (1–9) in 6797 documents. The highest median (interquartile range) number of citations was 8 (2.7–12.7) for France, followed by 7.5 (2–22.5) for Iran and 6 (3–13.5) for the United Kingdom. The country most often citing articles that were published in Human & Experimental Toxicology was the United States, which made citations in 1508 documents, followed by India with citations in 792 documents. CONCLUSION: The documents in Human & Experimental Toxicology focus principally on original data, with very few review articles. Review articles tend to have higher citation rates than original articles, and hence, the editors and authors of Human & Experimental Toxicology might usefully promote the submission of reviews in the future to improve the impact of the journal.